Digital Learning Environments: New Possibilities and Opportunities - Peters, Otto (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2000)
This paper deals with the general problem whether and, if so, how far the impact of the digitised learning environment on our traditional distance education will change the way in which teachers teach and learners learn. Are the dramatic innovations a menace to established ways of learning and teaching or are they the panacea to overcome some of the difficulties of our system of higher learning and to solve some of our educational problems caused by the big and far-reaching educational paradigm shift? This paper will not deal with technical or technological achievements in the field of information and communication which are, of course, revolutionary and to be acknowledged and admired. Rather, the digital learning environment will be analysed from a pedagogical point of view in order to find out what exactly are the didactic possibilities and opportunities and what are its foreseeable disadvantages.